Synergistic mixture of Parthenium hysterophorus L. extract and potassium iodide as a novel efficient composite inhibitor on steel corrosion in sulfuric acid - Hao Wu; Shuduan Deng; Dandan Shao; Gaofei Wei; Juan Xu; Xianghong Li (Journal of Materials Research and Technology)
The extract of Parthenium hysterophorus L. (PHLE), derived from the invasive weed, contains flavonoids, phenylpropanoids, alkaloids, and amino acids. Weight loss tests demonstrated that PHLE moderately inhibited corrosion of cold rolled steel (CRS) in 0.50 M H2SO4, with a maximum efficiency of 74.45%. The inhibition efficiency increased to 91.51% with the addition of a small amount of KI (10 mg L−1). The adsorption of PHLE and PHLE/KI followed Langmuir isotherm, and the electrochemical mechanism suggested that PHLE/KI acted as a mixed-type inhibitor with geometric blocking effects. Nyquist plots showed a large capacitive loop and increased charge transfer resistance for PHLE/KI. Surface analysis indicated reduced surface roughness and increased hydrophobicity with PHLE/KI. Elemental analysis revealed that PHLE compounds adsorbed on the CRS surface via physisorption and chemisorption, driven by conjugated structures and N and O atoms. Quantum chemical and molecular dynamics simulations confirmed that PHLE's components can effectively protect CRS through coordination and feedback bonds. The addition of trace KI enhanced the inhibition effect, offering significant potential for cost-effective plant-based inhibitors.